Comparing sensory processing in children with Down syndrome to a mental age matched sample of children with autism, other developmental disabilities, and typically developing children. (March 2023) - Isralowitz, Elizabeth B.; Sideris, John; Stein Duker, Leah I.; Baranek, Grace T.; Cermak, Sharon A.
Abstract: Background: Atypical sensory processing impacts children with intellectual and developmental disabilities (IDD). Research has focused on SP in individuals with autism spectrum disorder (ASD); comparatively, little has been written regarding individuals with Down syndrome (DS) and IDDs. Aims: We compared patterns of sensory processing in children with DS to children with ASD, other IDDs, and typically developing (TD) peers examining the relationship among different sensory processing measures. Methods and procedures: We analyzed cross-sectional data using two caregiver questionnaires (SP, SEQ) and one observational measure (SPA). Groups were compared on three sensory processing patterns: hyporesponsiveness; hyperresponsiveness; and sensory interests, repetitions, and seeking (SIRS) via ANOVA. We assessed concordance through correlations. Outcomes and results: Children with DS, IDD, and ASD demonstrated more atypical sensory processing behaviors than TD peers. Children with ASD exhibited the most atypical responses across all measures, significantly more than DS children on all but one subscale. The IDD and DS groups differed on several measures. Measurement concordance was higher between caregiver-report versus observational assessment. Conclusions and implications: Differences between three clinical groups indicate that sensory processing features may differ across clinical populations regardless of cognitive functioning. Lower concordance between caregiver-report and observation measures highlights the need to understand sensory processing expression across different tasks and environments. Highlights: Children with Down syndrome display unique sensory characteristics. Children with ASD exhibited more sensory features than TD, DS, and other IDDs. Researchers and clinicians need to distinguish different clinical phenotypes. Low correlation between caregiver-report and researcher observation measures. Using report and direct measures improves our understanding of sensory features.